2021
DOI: 10.3390/v13071372
|View full text |Cite
|
Sign up to set email alerts
|

A New Enterobacter cloacae Bacteriophage EC151 Encodes the Deazaguanine DNA Modification Pathway and Represents a New Genus within the Siphoviridae Family

Abstract: A novel Enterobacter cloacae phage, EC151, was isolated and characterized. Electron microscopy revealed that EC151 has a siphovirus-like virion morphology. The EC151 nucleotide sequence shows limited similarity to other phage genomes deposited in the NCBI GenBank database. The size of the EC151 genome is 60,753 bp and contains 58 putative genes. Thirty-nine of them encode proteins of predicted function, 18 are defined as hypothetical proteins, and one ORF identifies as the tRNA-Ser-GCT-encoding gene. Six ORFs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Instead, phages are also described as polyvalent, as presented by Finney et al (2022), with phages lysing both Enterobacter spp. and Klebsiella aerogenes [ 73 ], or by Addablah et al (2021), with phages infecting E. cloacae and E. coli simultaneously [ 74 ]. Jamal et al (2018) reported the phage MJ2, which was able to inhibit the growth of E. cloacae , Achromobacter xylosoxidans , K. pneumoniae , and P. aeruginosa [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, phages are also described as polyvalent, as presented by Finney et al (2022), with phages lysing both Enterobacter spp. and Klebsiella aerogenes [ 73 ], or by Addablah et al (2021), with phages infecting E. cloacae and E. coli simultaneously [ 74 ]. Jamal et al (2018) reported the phage MJ2, which was able to inhibit the growth of E. cloacae , Achromobacter xylosoxidans , K. pneumoniae , and P. aeruginosa [ 75 ].…”
Section: Discussionmentioning
confidence: 99%